USING CHLOROFLUOROCARBONS (CFCS) AND SULPHUR HEXAFLUORIDE (SF6) TO CHARACTERISE GROUNDWATER MOVEMENT AND RESIDENCE TIME IN A LOWLAND CHALK CATCHMENT - Gooddy D.C.; Darling W.G.; Abesser C.; Lapworth D.J. (My University, 2006)
Chlorofluorocarbons (CFCs) and sulphur hexafluoride (SF6) provide a technique for dating groundwaters up to 50 years old. When used together, CFCs and SF6 can help to resolve the extent to which groundwater mixing occurs, and therefore provide indications of the likely groundwater flow mechanisms. Modelling shows that diffusive retardation of these age tracers is likely to be low owing to the high moisture content of the chalk unsaturated zone. Data collected from groundwater and surface water from a lowland Chalk catchment in southern England suggest that groundwater movement can be divided into three regimes: on the interfluves of the catchment, 'piston' flow dominates, with a bulk groundwater age of several decades; at the valley bottom, there is mixing between shallow groundwater and stream water; and in an intermediate zone between the top and the bottom of the valley there is approximately 3:1 mixing between new and pre-tracer groundwaters. A conceptual model of groundwater movement has been developed to describe the catchment processes. Surface water-groundwater interactions are found to take place down to depths in excess of 10 m bgl. The nitrate found at the greatest depth is thought to date from the mid-1950s. © 2006 Daren C. Gooddy.
Keywords: CATCHMENT PROCESSES; CFCS; CHALK; GROUNDWATER MIXING; LOCAR; RESIDENCE TIME; SF; SURFACE WATER-GROUNDWATER INTERACTION